ANALISIS PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDesa) DI DESA TANJUNG RAJA KECAMATAN STM HULU KABUPATEN DELI SERDANG - Tio Fanta Purba; Mas’ut . (Universitas Islam Islam Sumatera Utara, 2021)
This study aims to see the implementation of APBDes and village openness to the people of Tanjung Raja Village, STM Hulu district, Deli Serdang Regency during the 2017-2018 period. The type of research used in this research in qualitative research, while the research method used is descriptive method. The data collection tecniques carried out were by observing the field (Tanjung Raja Village Head, Treasurer, village officials and also the Tanjung Raja Village community. In addition, the documentation technique is to collect data related to APBDes and other influential documents. The sample in this study was in one sample, namely Tanjung Raja village, STM Hulu District, Deli Serdang Regency. This research proves that the preparation of APBDes in Tanjung Raja village is in accordance with the rules set by government. However, there are still things that need to be improved, such as the absence of Bumdes in Tanjung Raja village.